Evaluation of the diagnostic value of contrast-enhanced voiding urosonography with regard to the further therapy regime and patient outcom: A single-center experience in an interdisciplinary uroradiological setting - Marschner, Constantin; Schwarze, Vincent; Stredele, Regina; Froelich, Matthias F.; Rübenthaler, Johannes; Geyer, Thomas; Clevert, Dirk-André (Medicina, 2021)
Background and Objectives: Vesicoureteral reflux (VUR) describes a common pediatric anomaly in pediatric urology with a prevalence of 1–2%. In diagnostics, in addition to the gold standard of voiding cystourethrography (VCUG), contrast-enhanced urosonography (ceVUS) offers a radiation-free procedure, which, despite its advantages, is not yet widely used. In the present single-center study, subsequent therapeutic procedures and outcomes after ceVUS of 49 patients were investigated. The aim of the study is to investigate the efficacy of ceVUS with the intention of broader clinical implementation. Materials and Methods: Between 2016 and 2020, 49 patients were retrospectively included and received a ceVUS to evaluate VUR. With a distribution of 47:2 (95.9%), a clear female predominance was present. The age of the patients varied between 5 months and 60 years at the time of ceVUS. All examinations were all performed and subsequently interpreted by a single experienced radiologist (EFSUMB level 3). Results: Compared to intraoperative findings, ceVUS shows a sensitivity of 95.7% with a specificity of 100%. Allergic reactions to the contrast medium could not be observed. Conclusion: With its high sensitivity and intraoperative validation, ceVUS offers an excellent alternative to VCUG, the gold standard in the diagnosis of VUR. In addition, ceVUS is a radiation-free examination method with a low risk profile that offers an exceptional diagnostic tool in the diagnostic clarification of recurrent urinary tract infections with the suspected diagnosis of VUR and should also be included in the consideration of a diagnosis next to the established VCUG, especially in younger children.
Gesehen am 14.05.2021